2011
DOI: 10.1111/j.1556-4029.2010.01652.x
|View full text |Cite
|
Sign up to set email alerts
|

Sex Determination from Hand and Foot Dimensions in a North Indian Population

Abstract: Hands and feet are often recovered from the site of natural as well as man-made disasters because of bomb blasts, train accidents, plane crashes, or mass homicides. This study is intended to establish standards for determination of sex from the dimensions of hands and feet in a North Indian population. The data for this study comprise 123 men and 123 women aged between 17 and 20 years from the "Rajput" population of Himachal Pradesh in North India. Four anthropometric measurements viz. hand length, hand breadt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
52
2
6

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(77 citation statements)
references
References 36 publications
17
52
2
6
Order By: Relevance
“…It is not uncommon to find the peripheral parts of the body such as hand and foot in mass disasters, and assault cases where the body is dismembered to conceal the identity of the victim. When an individual hand is recovered and brought for examination, somatometry of the hand, osteological and radiological examination can help in the determination of primary indicators of identification such as sex, age and stature [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Accurate sexing of the human remains primarily narrows down the pool of possible victim matches and thus helps the investigation.…”
Section: Introductionmentioning
confidence: 99%
“…It is not uncommon to find the peripheral parts of the body such as hand and foot in mass disasters, and assault cases where the body is dismembered to conceal the identity of the victim. When an individual hand is recovered and brought for examination, somatometry of the hand, osteological and radiological examination can help in the determination of primary indicators of identification such as sex, age and stature [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Accurate sexing of the human remains primarily narrows down the pool of possible victim matches and thus helps the investigation.…”
Section: Introductionmentioning
confidence: 99%
“…At the age of 18 years, the adult stature and foot size are attained its full growth. Therefore, individuals selected for this study were above 18 years [14].…”
Section: Discussionmentioning
confidence: 99%
“…Stature estimation is an important constraint in identification of mutilated and skeletal remains which could be helpful in the investigation of the identity of victims of mass disasters and fatal assaults cases [9]. Some previous studies have shown the relationship between various parts of the body with the stature and sex [10][11][12][13][14][15]. In forensic investigations, sex, age, and stature of an individual can be determined by the measurement of hand and foot dimension [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Этому способствуют колоссальная вариативность формы стопы, отсутствие четких представлений об анатомической и функциональной норме сто-пы, расплывчатость понятия о функциональной недостаточности стопы, а также сложность ре-гистрации параметров функции стопы, которые связаны с ходьбой человека [3]. Поэтому сохра-няет актуальность определение индивидуаль-но-типологической изменчивости морфологии и функции интактной стопы.…”
Section: Introductionunclassified